2019
DOI: 10.3389/fimmu.2019.01325
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecules and Immune Checkpoints Are Differentially Expressed on Different Subsets of Dendritic Cells

Abstract: Dendritic cells (DCs) play a crucial role in initiating and shaping immune responses. The effects of DCs on adaptive immune responses depend partly on functional specialization of distinct DC subsets, and partly on the activation state of DCs, which is largely dictated by environmental signals. Fully activated immunostimulatory DCs express high levels of costimulatory molecules, produce pro-inflammatory cytokines, and stimulate T cell proliferation, whereas tolerogenic DCs express low levels of costimulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 71 publications
(90 reference statements)
3
56
0
Order By: Relevance
“…Furthermore, PD-L1/CD274 silencing on DC could enhance T-cell responses leading to tumor clearance [ 2 ], which is in accordance with several studies demonstrating the advantages of knocking down PD-L1/CD274 regarding the efficacy of DC vaccine therapy [ 27 , 28 ]. Whereas a negligible PD-L1/CD274 expression of blood pDC and mDC of healthy donors has been described [ 29 ], blood DC of lung cancer patients show a clear PD-L1/CD274 expression in this study, thereby confirming the data of blood DC in patients with ovarian cancer [ 2 ] and melanoma [ 30 ]. Similarly, monocytes in healthy controls express only a small amount of PD-L1/CD274, whereas monocytes in cervical cancer patients show an increased expression [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, PD-L1/CD274 silencing on DC could enhance T-cell responses leading to tumor clearance [ 2 ], which is in accordance with several studies demonstrating the advantages of knocking down PD-L1/CD274 regarding the efficacy of DC vaccine therapy [ 27 , 28 ]. Whereas a negligible PD-L1/CD274 expression of blood pDC and mDC of healthy donors has been described [ 29 ], blood DC of lung cancer patients show a clear PD-L1/CD274 expression in this study, thereby confirming the data of blood DC in patients with ovarian cancer [ 2 ] and melanoma [ 30 ]. Similarly, monocytes in healthy controls express only a small amount of PD-L1/CD274, whereas monocytes in cervical cancer patients show an increased expression [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we found that while PD‐L1 expression is increased on peripheral DC and monocytes during VTD treatment, combination with the anti‐CD38 monoclonal antibody Dara seems to prevent this phenomenon. In fact, it has been reported that inflammation can lead to an increased expression of PD‐L1 on DC, suggesting that inflammation induced by chemotherapy could be responsible for the increase PD‐L1 expression observed in the control group upon treatment . In contrast, in the Dara group, as DC subsets are continuously depleted by Dara, we hypothesized that the low PD‐L1 expression was the reflect of the expression level on de novo produced DC.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, it has been reported that inflammation can lead to an increased expression of PD-L1 on DC, suggesting that inflammation induced by chemotherapy could be responsible for the increase PD-L1 expression observed in the control group upon treatment. 22 In contrast, in the Dara group, as DC subsets are continuously depleted by Dara, we hypothesized that the low PD-L1 expression was the reflect of the expression level on de novo produced DC. Given the important expression of Fc receptors (FcR) on DC, 23 we cannot exclude that the anti-CD38 monoclonal antibody may react simultaneously on the same cell via their binding site and also via FcR by implementing the so-called scorpion effect.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, we developed an 18-color flow cytometric panel dedicated to the analysis of DCs (a representative analysis showing the gating strategy is reported in Fig. 1) and demonstrated that cDC1s, cDC2s, and pDCs have also a differential expression of inhibitory molecules, with cDC1s having a unique immune checkpoint repertoire characterized by high expression of T-cell immunoglobulin and mucin-domain containing-3 (TIM-3, CD366), low PD-L1 expression, and lack of ILT2 (48). Notably, this unique repertoire was subverted in patients affected by myelodysplastic syndromes, suggesting that the analysis of PBDC phenotype may be helpful to provide new insights in the comprehension of the role played by distinct DC subsets in the pathogenesis and progression of different types of cancer (48).…”
Section: Characterization Of Peripheral Blood Dcs In Cancer Patientsmentioning
confidence: 99%